Lasting effects of repeated rTMS application in focal hand dystonia - Borich, Michael (Restor Neurol Neurosci, 2009)
PURPOSE: Focal hand dystonia (FHD) is a rare but potentially devastating disorder involving involuntary muscle spasms and abnormal posturing that impairs functional hand use. Increased cortical excitability and lack of inhibitory mechanisms have been associated with these symptoms. This study investigated the short- and long-term effects of repeated administrations of repetitive-transcranial magnetic stimulation (rTMS) on cortical excitability and handwriting performance. METHODS: Six subjects with FHD and nine healthy controls were studied. All subjects with FHD received rTMS (1Hz) to the premotor cortex (PMC) for five consecutive days; of those, three subjects received five days of sham rTMS completed ten days prior to real treatment. Healthy subjects received one real rTMS session. Cortical silent period (CSP) and measures of handwriting performance were compared before and after treatment and at ten-day post-treatment follow-up. RESULTS: At baseline, significant differences in CSP and pen pressure were observed between subjects with FHD and healthy controls. Differences in CSP and pen velocity between subjects in real and sham rTMS groups were observed across treatment sessions and maintained at follow-up. CONCLUSIONS: After five days of rTMS to PMC, reduced cortical excitability and improved handwriting performance were observed and maintained at least ten days following treatment in subjects with FHD. These preliminary results support further investigation of the therapeutic potential of rTMS in FHD.